Impact of weather-influenced urban mobility on carbon footprint of Spanish healthcare centres. (March 2021) - Sánchez-Barroso, G.; González-Domínguez, J.; García-Sanz-Calcedo, J.; Sokol, M.
Abstract: Introduction: Weather conditions influence urban mobility and alter greenhouse gas emissions. The aim of this paper is to analyse the impact of carbon footprint derived from the use of private vehicles in Extremadura (Spain), focusing on weather-influenced transport to rural healthcare centres. This new understanding will help to improve predictions of the impact of anthropogenic emissions. Methods: A retrospective research method was proposed to analyse the surveys carried out between April-2019 and March-2020 in three healthcare centres where the number of users are ranged from 5376 to 11, 980. A total of 22, 541 patients were interviewed about the vehicle utilised to receive health assistance. Furthermore, average temperature, mean relative humidity and quantity of rain were collected to examine the correlation with CO2 emissions from transport. Results: Mathematical expressions are proposed to estimate the daily CO2 emissions per user as a function of both temperature and relative humidity. The variation rate in the amount of emissions with respect to weather conditions is quantified. Emissions significantly decreased by 25% due to an increase of transport on foot at temperatures above 20 °C and relative humidity below 60%. The relationship between climate variables and transport mode choice is discussed to formulate policies and strategies that stimulate active transport. Conclusion: The influence of meteorological conditions was quantified separately, which were −8.6 g CO2 eq/°C, +3.4 g CO2 eq/%RH and +8.8 g CO2 eq/mm rain. The findings of this research provide information to expand scope of Life Cycle Analyses of health infrastructures. Highlights: Weather conditions influence urban mobility and alter greenhouse gas emissions. A mathematical modelling was developed to estimate the daily CO2 emissions. The change rate in emissions related to weather conditions was quantified. This research supports the decision-making in health care planning departments.